Assessing Hubbard-corrected AM05+U and PBEsol+U density functionals for strongly correlated oxides CeO2 and Ce2O3. Issue 38 (19th September 2016) - Weck, Philippe F.; Kim, Eunja
Abstract : The structure–property relationships of bulk CeO2 and Ce2 O3 have been investigated within the DFT+ U framework. AM05+ U and PBEsol+ U reproduce experimental crystalline parameters and properties with superior accuracy compared to conventional Hubbard-corrected exchange–correlation functionals. Abstract : The structure–property relationships of bulk CeO2 and Ce2 O3 have been investigated using AM05 and PBEsol exchange–correlation functionals within the frameworks of Hubbard-corrected density functional theory (DFT+ U ) and density functional perturbation theory (DFPT+ U ). Compared with conventional PBE+ U, RPBE+ U, PW91+ U and LDA+ U functionals, AM05+ U and PBEsol+ U describe experimental crystalline parameters and properties of CeO2 and Ce2 O3 with superior accuracy, especially when + U is chosen close to its value derived by the linear-response approach. The present findings call for a reexamination of some of the problematic oxide materials featuring strong f- and d-electron correlation using AM05+ U and PBEsol+ U .